2017
DOI: 10.1038/npp.2017.246
|View full text |Cite
|
Sign up to set email alerts
|

The Limbic System in Youth Depression: Brain Structural and Functional Alterations in Adolescent In-patients with Severe Depression

Abstract: Adolescent-onset major depressive disorder (MDD) is associated with an increased risk of recurrent depressive episodes, suicidal behaviors, and psychiatric morbidity throughout the lifespan. The objective of the present study was to investigate brain structural and functional changes in adolescent patients with MDD. Furthermore, we aimed to clarify the influence of early-life stress on brain function and structure. The study investigated adolescent patients with severe MDD (n=20, mean age=16.0, range=15-18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 57 publications
3
54
1
1
Order By: Relevance
“…The brain tissues were isolated, washed with ice‐cold PBS, and immediately immersed in liquid nitrogen. As previous studies have pointed out the functional and structural alterations in the limbic area, including cerebral cortex and amygdala, in mouse models of depression and in adult patients with major depressive disorder, the limbic area of mice brain was focused to determine the mechanisms of anti‐depressant‐like effects of FA. The entire limbic area of the mouse brain containing the cortex, hippocampus, and amygdale was quickly dissected on ice and was minced for RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The brain tissues were isolated, washed with ice‐cold PBS, and immediately immersed in liquid nitrogen. As previous studies have pointed out the functional and structural alterations in the limbic area, including cerebral cortex and amygdala, in mouse models of depression and in adult patients with major depressive disorder, the limbic area of mice brain was focused to determine the mechanisms of anti‐depressant‐like effects of FA. The entire limbic area of the mouse brain containing the cortex, hippocampus, and amygdale was quickly dissected on ice and was minced for RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Magnesium deficiency has been shown to lead to changes in the functioning of the central nervous system (CNS), especially in the glutamatergic transmission in the limbic system and cerebral cortex [ 54 ]—brain regions that play important roles in the etiopathogenesis of depression [ 96 , 97 , 98 ]. Magnesium is particularly well known for its importance as an antagonist of the NMDA glutamate receptor, which has long been understood as a key player in synaptic potentiation, learning and memory [ 99 , 100 ].…”
Section: Magnesiummentioning
confidence: 99%
“…Evidence supporting this hypothesis can also be derived from previous studies. First, higher BDNF DNA methylation has also been found in MDD patients (Kang et al, ), a diagnosis frequently associated with high amygdala reactivity (Redlich et al, ; Redlich et al, ; Stuhrmann et al, ). Second, it has been shown that the intake of epigenetic modifying medicaments like citalopram increases peripheral BDNF levels (Lopez et al, ) which goes along with reduced amygdala reactivity (Murphy, Norbury, O'Sullivan, Cowen, & Harmer, ).…”
Section: Discussionmentioning
confidence: 99%